From lockdown to limelight: unexpected gains in information seeking and scholarly communication research - Deja, Marek (Information Research an international electronic journal, 2025)
Introduction. This study investigates the impact of COVID-19 on the impact of research in information seeking and scholarly communication. Method. An analysis of bibliometric data was performed focusing on publications related to information seeking and scholarly communication, using the SciVal tool to extract documents related to the topic cluster published from 2015 to 2022. To establish causality, the C-ARIMA model was applied to allow a comparison between actual post-pandemic research metrics and counterfactual predictions. Analysis. Analysing key metrics such as the Field-weighted citation impact (FWCI), the study sought to quantify the causal relationship between the pandemic and changes in research output, while accounting for prior trends and seasonal publishing cycles. Results. The results showed a significant increase in FWCI after the pandemic. This growth was not a random event; the model also demonstrated that this was a time-dependent outcome of the pandemic’s influence on research impact. Conclusion(s). The pandemic provided a substantial boost to the impact of research related to information seeking and scholarly communication. This may be largely driven by an increased need for accessible information, marking a significant shift in academic priorities after the global crisis.